2014
DOI: 10.1590/1519-6984.01413
|View full text |Cite
|
Sign up to set email alerts
|

Helminths and Pentastomida of two synanthropic gecko lizards, Hemidactylus mabouia and Phyllopezus pollicaris, in an urban area in Northeastern Brazil

Abstract: Helminths and pentastomids were examined in exotic Hemidactylus mabouia and native Phyllopezus pollicaris lizards, living synanthropically in an urban area in the municipality of Crato, Ceará state, northeastern Brazil. A total of 194 lizards were collected, being 76 specimens of H. mabouia e 118 specimens of P. pollicaris. Six parasite species were found infecting H. mabouia: the cestode Oochoristica sp., the nematodes Parapharyngodon sceleratus, Physaloptera retusa, Physalopteroides venancioi, and Spauligodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Nevertheless, records for S. intermedia were restricted so far to a teid Ameivula nativo (Rocha, Bergallo & Peccinini-Seale, 1997) Little is known about the biology of the genus Oochoristica. Most studies on the genus were limited to describe new species and record new hosts (Ávila & Silva 2010;Brito et al 2014b;Sousa et al 2014). Our study reports three records of hosts (P. pollicaris, H. agrius and H. brasilianus) with two new infection records for the genus Oochoristica.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, records for S. intermedia were restricted so far to a teid Ameivula nativo (Rocha, Bergallo & Peccinini-Seale, 1997) Little is known about the biology of the genus Oochoristica. Most studies on the genus were limited to describe new species and record new hosts (Ávila & Silva 2010;Brito et al 2014b;Sousa et al 2014). Our study reports three records of hosts (P. pollicaris, H. agrius and H. brasilianus) with two new infection records for the genus Oochoristica.…”
Section: Discussionmentioning
confidence: 88%
“…Currently, there are 23 genera of helminths recognized as parasites of the lizard families Phyllodactylidae and Gekkonidae (Anjos et al 2005;Ávila & Silva 2010;Ávila et al 2010;Brito et al 2014a;Sousa et al 2014;Cazorla & Morales Moreno 2015;Bezerra et al 2016; this study); for the Caatinga biome, about 10 species of helminths have already been reported with a prevalence above 50% (Anjos et al 2005;Avila et al 2012;Brito et al 2014b;Sousa et al 2014; this study), and there were four helminth species with prevalences below 60% for deserts and coastal areas in Peru (Goldberg & Bursey 2010); two species had prevalences of 33.3% in the Brazilian Amazon forest (Ávila & Silva 2013); two species had prevalences up to 22.8% in the Atlantic Forest (Ávila et al 2010;Almeida-Gomes et al 2012); and three helminth species had prevalences below 15% for the tropical thorny mountain areas of Venezuela (Cazorla & Morales Moreno 2015). Notwithstanding that some genera and species of helminths were previously reported for different biomes as parasites of geckos, as S. oxkutzcabiensis and all species of the genera Oochoristica and Parapharyngodon, almost all prevalences registered for them were below that obtained for the Caatinga biome [e.g., Oochoristica sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…furcocerca (Dias et al, 2005) and Micrablepharus maximiliani Reinhardt and Lütken, 1862 parasitized by R. mottae Almeida, Freire and Lopes (Almeida et al, 2009), all in restinga environments; Trachylepis atlantica (Schmidt, 1945) infected by R. freitasi (Motta and Gomes, 1968), in Fernando de Noronha Island, Pernambuco state. On the domain of Caatinga, Northeast Brazil, R. mottae and R. frenata Ali, Riley and Self, 1981 were found parasitizing Hemidactylus mabouia (Moreau de Jonnès, 1818) in human habitations (Anjos et al, 2007;Almeida et al, 2008c), the remaining records include only R. mottae infecting: Tropidurus hispidus (Spix, 1825) (Almeida et al, 2008a(Almeida et al, , b, 2009Brito et al, 2014), T. semitaeniatus (Spix, 1825) (Almeida et al, 2008b(Almeida et al, , 2009Brito et al, 2014), Phyllopezus periosus Rodrigues, 1986(Almeida et al, 2008bBrito et al, 2014), P. pollicaris (Spix, 1825) (Almeida et al, 2008b;Sousa et al, 2010Sousa et al, , 2014Brito et al, 2014), M. arajara Rebouças-Spieker, 1981(Ribeiro et al, 2012a, and H. mabouia (Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%